The LIFE-ACE Framework of Building Therapeutic Relationships that Support Recovery in Japanese Community Mental Health: A Qualitative Study - Satoshi Okumura; Fujika Katsuki; Rintaro Imafuku (Community Mental Health Journal, 2026)
Abstract Recovery-oriented practice emphasizes collaborative, person-centered relationships. However, culturally grounded frameworks describing how therapeutic relationships support recovery in Japan remain limited. This study explored the perspectives of Japanese community mental health service users to identify relational components that facilitate recovery and develop a culturally responsive conceptual framework. Using a phenomenological-qualitative design, semi-structured interviews were conducted with ten service users receiving community-based care. The data were analyzed through reflexive thematic analysis. Seven components were identified and organized into a two-stage structure. The listening, individuality, friendliness, and empowerment (LIFE) stage describes relational processes that build psychological safety through respectful communication, personal identity recognition, approachable interpersonal interaction, and self-determined decision-making support. The awareness, commitment, and exposure (ACE) stage captures subsequent processes that promote recovery-oriented action, including gaining new perspectives, setting and pursuing personally meaningful goals, and engaging in social roles and group interactions. Together, the LIFE-ACE framework illustrates the transformation of therapeutic relationships from trust-building to fostering social participation. It aligns with recovery principles while reflecting Japanese cultural values such as interpersonal harmony, empathy, and relational subtlety. The findings highlight the importance of approachable communication, recognition of individuality, and supportive opportunities for social engagement in cultivating recovery-oriented practice. The framework offers practical guidance for mental health professionals seeking to create culturally responsive therapeutic relationships that enhance psychological safety, autonomy, and meaningful participation in community life.